Improving students' attitudes toward science by using the discovery learning model on ecology and biodiversity topics - Aprillia, Sakinah; Winarno, Nanang; Damopolii, Insar; Aritonang, Rika Magdalena (IAIN Palangka Raya, 2025)
The purpose of this study was to analyze the increase in students' Attitudes toward Science by using the Discovery Learning model on the topic of ecology and biodiversity. The method used in this research is the pre-experimental method with One Group Pretests-Posttests. The research instrument used in this study is the Arabic-Speaking Students Attitudes toward Science Survey (ASSASS) questionnaire. This research was conducted in one of the schools in Bandung City with a total of 30 research subjects in class VII, consisting of 12 boys and 18 girls. This study's results indicate a significant increase in Attitude Toward Science of students with an average pretest of 53% and posttest of 70%, which is indicated by a total N-Gain score of 0.30 (sufficient). The N-Gain score on the attitude toward science and science learning indicator is 0.27 (low), the Unfavorable outlook indicator is 0.29 (low), the Control belief indicator is 0.26 (low), and the Behavioral belief indicator is 0.32 (sufficient). The Intention indicator is 0.37 (sufficient). Based on the results of this study, the implementation of the Discovery Learning model can be an alternative learning model in improving students' attitudes toward Science.